Modified anaerobic digestion elutriated phased treatment for the anaerobic co-digestion of sewage sludge and food wastewater. Issue 3 (1st February 2017) - Mo, Kyung; Lee, Wonbae; Kim, Moonil
ABSTRACT: A modified anaerobic digestion elutriated phased treatment (MADEPT) process was developed for investigating anaerobic co-digestion of sewage sludge and food wastewater. The anaerobic digestion elutriated phased treatment (ADEPT) process is similar to a two-phase system, however, in which the effluent from a methanogenic reactor recycles into an acidogenic reactor to elutriate mainly dissolved organics. Although ADEPT could reduce reactor volume significantly, the unsolubilized solids should be wasted from the system. The MADEPT process combines thermo-alkali solubilization with ADEPT to improve anaerobic performance and to minimize the sludge disposal. It was determined that the optimal volume mixing ratio of sewage sludge and food wastewater was 4 : 1 for the anaerobic co-digestion. The removal efficiencies of total chemical oxygen demand, volatile solids, and volatile suspended solids in the MADEPT process were 73%, 70%, and 64%, respectively. However, those in the ADEPT process were only 48%, 37%, and 40%, respectively, at the same hydraulic retention time (HRT) of 7 days. The gas production of MADEPT was two times higher than that of ADEPT. The thermo-alkali solubilization increased the concentration of dissolved organics so that they could be effectively degraded in a short HRT, implying that MADEPT could improve the performance of ADEPT in anaerobic co-digestion.